THE PERCEPTIONS OF ISLAMIC BOARDING SCHOOL GUARDIANS, ACCOUNTING STUDENTS, AND NON-ACCOUNTING STUDENTS ON THE ETHICS OF PREPARING FINANCIAL STATEMENTS BASIS DE PSAK 112 (CASE STUDY OF ISLAMIC SCHOOLS IN PEKALONGAN) - Pribadi, Tegar Hary (Media Mahardhika, 2024)
This research aims to examine the ethics of financial reporting based on PSAK 112 in the context of Islamic boarding schools (pondok pesantren) in Pekalongan. The ethical aspects considered include earnings management, misstatement, disclosure, cost and benefit, and responsibility in financial reporting. The study is conducted directly within the environment of Islamic boarding schools in both the city and regency of Pekalongan. The respondents include 113 caretakers of Islamic boarding schools, 70 accounting students, and 73 non-accounting students. The analytical tool applied for hypothesis testing (H1, H2, H3, and H4) is ANOVA. The findings of this research reveal that there is no significant differentiation in the perception of ethical practices in financial reporting among caretakers of Islamic boarding schools, accounting students, and non-accounting students. However, there is differentiation in the perception regarding misstatement and responsibility in the presentation of financial statements. Moreover, there is differentiation in the perception of complying with Law No. 18 of 2019 concerning Islamic Boarding Schools (Ponpes). Additionally, there is differentiation in the understanding of the PSAK Accounting Standards for Islamic Boarding Schools among the caretakers, accounting students, and non-accounting students.